2017
DOI: 10.15405/epsbs.2017.10.23
|View full text |Cite
|
Sign up to set email alerts
|

Inculcating Spiritual Intelligence To Enhance Students’ Psychological Wellbeing

Abstract: Students who have psychological problems in their lives may also have problems in their academic performance. Inculcating Spiritual Intelligence (SI) is believed to be able to overcome psychological problems (Piedment, 2001) such as depression, anxiety and stress. However, not every student has the inspiration and knowledge to enhance their own SI. At Universiti Malaysia Pahang (UMP), a module has been developed for this purpose. The UMP SI module focuses on Islamic values to enhance the role of `Man as Caliph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…SQ can also prepare students to solve problems in their academic performance, achieve their life goals, and improve their social life [30]. It is also highlighted by other researchers [31], [32] that studied students' psychological well-being and concluded that SQ values generally enhance students' emotions in a relationship, while also showing more positive behavior and attitude towards others in that relationship. All the research studies lead to the following hypothesis: there is a positive and significant SQ influence on ESQ among academicians in private HEIs (H2).…”
Section: Introductionmentioning
confidence: 91%
“…SQ can also prepare students to solve problems in their academic performance, achieve their life goals, and improve their social life [30]. It is also highlighted by other researchers [31], [32] that studied students' psychological well-being and concluded that SQ values generally enhance students' emotions in a relationship, while also showing more positive behavior and attitude towards others in that relationship. All the research studies lead to the following hypothesis: there is a positive and significant SQ influence on ESQ among academicians in private HEIs (H2).…”
Section: Introductionmentioning
confidence: 91%
“…Selain itu, kajian Mohamed, Seman, dan Abdul Wahab (2010) yang melibatkan responden di kalangan pelajar UMP menunjukkan terdapat segelintir pelajar yang mempunyai tahap amalan beragama yang rendah. Rani et al (2017) yang telah membangunkan Modul Kecerdasan Spiritual bagi pelajar-pelajar UMP menambah bahawa pelajar di universiti ini perlu ditingkatkan kecerdasan spiritual mereka.…”
Section: Latar Belakang Dan Pernyataan Masalahunclassified